1980
DOI: 10.1111/j.1471-4159.1980.tb06268.x
|View full text |Cite
|
Sign up to set email alerts
|

Accumulations of Cyclic AMP in Adenine‐Labeled Cell‐free Preparations from Guinea Pig Cerebral Cortex: Role of α‐Adrenergic and H1‐Histaminergic Receptors

Abstract: Norepinephrine, histamine, adenosine, glutamate, and depolarizing agents elicit accumulations of radioactive cyclic AMP from adenine-labeled nucleotides in particulate fractions from Krebs-Ringer homogenates of guinea pig cerebral cortex. The particulate fractions contain sac-like entities, which apparently are associated with a significant portion of the membranal adenylate cyclase. Particulate fractions from sucrose homogenates are a less effective source of such responsive entities. Activation of the adenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(40 citation statements)
references
References 26 publications
3
37
0
Order By: Relevance
“…These findings indicate a multiple localization of histamine'receptors and suggest that at least one part of the receptors is associated with neurons. There is also evidence that both neuronal and non-neuronal HA-receptors are coupled with specific adenylate cyclase systems [20][21][22].…”
Section: Discussionmentioning
confidence: 97%
“…These findings indicate a multiple localization of histamine'receptors and suggest that at least one part of the receptors is associated with neurons. There is also evidence that both neuronal and non-neuronal HA-receptors are coupled with specific adenylate cyclase systems [20][21][22].…”
Section: Discussionmentioning
confidence: 97%
“…For electron micrographs synaptoneurosomes of LRRK2-knockout mice were prepared as described above. The samples were fixed and processed as described previously (Daly et al, 1980;Hollingsworth et al, 1985) and embedded in Epon (Fluka, Munich, Germany). Ultrathin sections were cut on an ultra microtome (Reichert, Depew, NY, USA), contrasted in lead-uranyl acetate and imaged using a Zeiss EM10 transmission electron microscope (Zeiss, Oberkochen, Germany) operating with an acceleration voltage of 120 kV and connected to a CCD camera (1024 Â 1024 pixels; TVIPS GmbH, Gauting, Germany).…”
Section: Synaptoneurosome Preparation and Characterizationmentioning
confidence: 99%
“…There are some morphological criteria to identify synaptosomes, including small mitochondria within a sealed plasma membrane, synaptic vesicles present in nerve terminals, and an electron-dense membrane resembling postsynaptic membranes adhering to the periphery of the synaptosome (Whittaker, 1993). To achieve an enrichment in neuronal markers, several studies reported the use of a crude particulate fraction containing presynaptic and postsynaptic vesicularized components (Daly et al, 1980;Horn and Phillipson, 1976;Shimizu et al, 1975). The term synaptoneurosome is suggested for entities in which a presynaptic sac (synaptosome) is attached to a resealed postsynaptic sac (neurosome) Quinlan et al, 1999).…”
Section: Introductionmentioning
confidence: 99%